Balantidiasis: A Neglected Tropical Disease Used as a Study Model for a Holistic Approach to Sustainable Development in the Framework of Agenda 2030 Goals - Luca Nalbone (MDPI AG, 2021)
The term “sustainability” could be defined as the process of people maintaining changes in a homeostasis-balanced environment, in which the exploitation of resources, direction of investments, orientation of technological development, and institutional change are all in harmony. The most significant global effort to address sustainable development is the United Nations’ Sustainable Development Goals (SDGs). Among the various targets set within the 17 SDGs, the end of neglected tropical zoonoses (NTZs) is an example of how coordinated social, economic, and environmental efforts are needed to achieve this goal. Balantidiasis, caused by Balantidium coli, is a zoonotic parasitic disease characterized by high infection and incidence rates; however, it is only scantly investigated and therefore considered a NTZ. In this review article, balantidiasis was used as a model to demonstrate how proper management of NTZs falls in all the SDGs and how a holistic approach to animal and human diseases could improve their health status and other aspects of their being. In this manuscript, the SDGs were divided in three pillars: (i) social, (ii) economic, and (iii) eviromental. This theoretical division helps to demonstrate that the presence and, consequently, the control of an NTZ could be reflected on all the 17 SDGs.